Motor vehicles act, 1988 (New Delhi, 2012)
The first enactment relating to motor vehicles in India was the Indian Motor Vehicles Act, 1914, which was subsequently replaced by the Motor Vehicles Act, 1939. The Act of 1939 had been amended several times. Inspite of several amendments it was felt necessary to bring out a comprehensive legislation keeping in view the changes in the transport technology, pattern of passenger and freight movements, development of the road network in the country and particularly the improved techniques in the motor vehicles management. Various Committees as well as the Law Commission had gone into different aspects of road transport. Several Members of Parliament had also urged for comprehensive review of the Motor Vehicles Act, 1939. A Working Group was, therefore, constituted in January, 1984 to review all the provisions of the Act of 1939. This Working Group took into account the suggestions and recommendations earlier made by various bodies and institutions and made certain recommendations. On the recommendations of the Working Group State Governments were asked to submit their comments. The recommendations made by the Working Group and comments received from the State Governments were discussed at a special meeting of Transport Ministers of all States and Union Territories. Based on the conclusions reached in the meeting of Transport Ministers and suggestions made by the Supreme Court in a case the Motor Vehicles Bill was introduced in the Parliament.
Keywords: "Motor vehicles act, 1988"